Therapeutic Effect of Intestinal Autochthonous Lactobacillus reuteri P16 Against Waterborne Lead Toxicity in Cyprinus carpio - Giri, Sib Sankar; Yun, Saekil; Jun, Jin Woo; Kim, Hyoun Joong; Kim, Sang Guen; Kang, Jeong Woo; Kim, Sang Wha; Han, Se Jin; Sukumaran, V.; Park, Se Chang (Frontiers in Immunology, 2018)
Harmful effects of heavy metals are myriad. Lead (Pb) from soil and atmosphere contaminates water bodies and affects the aquatic animals. Our previous study confirmed the in vitro probiotic potential of Lactobacillus reuteri against Pb toxicity, but further investigation is necessary for gaining insights into the related protection mode. Therefore, in this study, we investigated the protective effects of the potential probiotic Lactobacillus reuteri P16 against waterborne Pb exposure-induced toxicity in the freshwater fish Cyprinus carpio. Fish (average weight: 23.16 ± 0.73 g) were allocated to four groups (control, Pb only, Pb + L. reuteri P16, and L. reuteri P16 only) and Pb groups wereexposed to waterborne Pb (1 mg L-1) for 6 weeks. L. reuteri P16 (108 CFU g-1) supplemented diet was provided twice daily. Growth performances, hemato-biochemical parameters, innate immune responses, intestinal microbiota, and Pb accumulation in tissues were measured at the end of the trial. When the fish were exposed to Pb, dietary supplementation of L. reuteri P16 effectively decreased mortality and accumulation of Pb in tissues, and improved the growth performance. Co-treatment with Pb and L. reuteri P16 alleviated Pb exposure-induced oxidative stress, reversed alterations in hemato-biochemical parameters, improved innate immune parameters, and restored intestinal enzymatic activities. Moreover, L. reuteri P16 supplementation reversed the changes in intestinal microbiota in Pb-exposed fish. Further, Pb exposure decreased the expressions of pro-inflammatory cytokines (TNF-α, IL-1β). However, the expression of heat shock proteins (HSP70 and HSP90) increased, which might have increased the cellular stress. Interestingly, the Pb-induced alterations of gene expressions were reversed by L. reuteri P16 supplementation. Thus, dietary administration of the potential probiotic L. reuteri P16 had several beneficial effects on growth performance and immune responses, decreased Pb-accumulation in tissues, and reversed alterations in hematological responses of C. carpio. Further, it offered direct protection against Pb-induced oxidative stress. Therefore, L. reuteri P16 may be a novel dietary supplement for enhancing growth performance and preventing Pb-exposure-induced toxicity in fish in aquaculture and aquatic products.